ATYPICAL EVOLUTION AFTER DENGUE: EXTRADURAL HEMATOMA OF VERTEBRAL CANAL LEVEL L4-L5 - ALBERTI,KAROLINE (2020)
ABSTRACT The objective of this paper is to report a case of atypical evolution after a classic case of dengue confirmed by serology, in which the formation of an epidural hematoma with low back pain and radiculopathy was observed. The article is a qualitative and descriptive case report. Data were collected from the medical records of the hospital where the patient was treated. In conclusion, the diagnostic correlation of dengue with this rare condition was possible due to radiological comparisons before and after the formation of the extradural hematoma. Level of evidence V; Expert Opinion.